2018
DOI: 10.1002/jper.17-0377
|View full text |Cite
|
Sign up to set email alerts
|

Influence of periodontal treatment on subgingival and salivary microbiotas

Abstract: Background: The purpose of this study was to characterize and compare subgingival

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
107
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 78 publications
(116 citation statements)
references
References 34 publications
7
107
2
Order By: Relevance
“…Since no previous data were available on salivary levels of NGAL and transferrin or the salivary microbiota in patients with psoriasis, the sample size was calculated using the clinical periodontal parameter, mean PPD. Based on findings from previous studies (Belstrøm et al, ; Üstün et al, ), the expected PPD in the periodontitis group was 3.4 ± 1.0 mm and the expected PPD in the psoriasis group was 2.8 mm. With fixed values of α = 0.05 and β = 0.10, the calculated sample size was n = 116, with 58 individuals in each group.…”
Section: Methodsmentioning
confidence: 78%
See 1 more Smart Citation
“…Since no previous data were available on salivary levels of NGAL and transferrin or the salivary microbiota in patients with psoriasis, the sample size was calculated using the clinical periodontal parameter, mean PPD. Based on findings from previous studies (Belstrøm et al, ; Üstün et al, ), the expected PPD in the periodontitis group was 3.4 ± 1.0 mm and the expected PPD in the psoriasis group was 2.8 mm. With fixed values of α = 0.05 and β = 0.10, the calculated sample size was n = 116, with 58 individuals in each group.…”
Section: Methodsmentioning
confidence: 78%
“…Notably, the majority of these bacterial species, including the proposed periopathogen P. gingivalis, were identified with higher relative abundance in patients with periodontitis. Salivary levels of P. gingivalis have been reported to associate with periodontitis (Damgaard et al, ), and previous studies have shown a positive correlation of salivary and subgingival levels of P. gingivalis (Belstrøm et al, ; Nickles, Scharf, Röllke, Dannewitz, & Eickholz, ) suggesting that the salivary microbiota reflects local bacterial alterations associated with periodontitis.…”
Section: Discussionmentioning
confidence: 98%
“…This study is part of a series of studies of a population, which has previously been described in detail [24]. Briefly, 31 patients with moderate to severe generalized periodontitis, as defined by the American Academy of Periodontology [25], were enrolled in the study.…”
Section: Study Populationmentioning
confidence: 99%
“…DNA isolation and next-generation sequencing were performed as previously described in detail [24]. In brief, bacterial DNA was isolated using MagNA Pure 96 instrument (Roche, Mannheim, Germany).…”
Section: Analysis Of Bacteriamentioning
confidence: 99%
See 1 more Smart Citation